COLORIMETER DEVELOPMENT WITH LIGHT DEPENDENT RESISTOR SENSOR - Yustar, Mhd
A Colorimeter with Light Dependent Resistor (LDR) sensor has been successfully developed. The Instrument consists of simple electrical components that easily obtained from electronic stores at a low price. This device consists of four parts, namely light emitting diodes (LED) as light source, cuvet container, light dependent resistor (LDR) as a detector, and a digital multimeter. In the measurement processes, the source of light was directed into sample solution, and the light that penetrates the solution was detected by the LDR. A multimeter was used to measure the changes of LDR conductivity. LDR electrical conductivity is proportional to the amount of light passing through the solution and can be converted into absorbance values. The performances of the instruments were tested with several standard solutions such as K2CrO4, K2Cr2O7, CuSO4, Co(CH3COO)2, and some food dye solutions. Linear calibration curves were found for all of the solutions and proved that complementary color was absorbed by the solutions. The results obtained with this colorimeter were in accordance with those obtained with commercial spectrophotometer at LEDs wave length. In the standard deviation value are 4,22%, 2,04 %, and 2,27% to blue, red, and yellow LED respectively. The colorimeter was used to analyze amylum and the results were compred to those obtained with commercial spectrophotometer. A 4,85% difference was found between the two results showing that the colorimeter has a good reliability. Developed colorimeter LDR sensor can be used as medium of learning/ simple practicum instrument at Senior High School.